Eletricidade para o ensino médio : enriquecendo o perfil conceitual dos estudantes sobre circuitos elétricos simples por meio da integração de simulações computacionais e experimentos reais - Bariani, Lucas Rocha (2022)
It is very important for Science Teaching that experimental activities are planned in a way that promotes the link between scientific theories and reality. Then, a TechnicalTechnological Product (or educational product) was elaborated in this work, which integrates computational activities, through computer simulations with the PhET online platform, and experimental activities, using the Arduino prototyping board, for Physics Teaching in High School, specifically for the study of electricity, focused on simple electrical circuits. The material focus at teachers interested in the implementation of active methods for alleviating students' alternative conceptions of electricity. The application and validation of the educational product were carried out with: a Licentiate class, a class of students from the 3rd grade of High School, and with Physics teachers, each moment with its particularities. In the applications of the product, the importance of experimental activities and the use of digital technologies in the classroom was reinforced, both with the use of Arduino and the use of the PhET online platform. In addition, there was an emphasis on the approach of alternative conceptions, indicating the importance of dealing with this issue in High School.